Promoter Architecture and Transcriptional Regulation of Genes Upregulated in Germination and Coleoptile Elongation of Diverse Rice Genotypes Tolerant to Submergence - Mohanty, Bijayalaxmi (Frontiers in Genetics, 2021)
Abstract Word Count: 335 Rice has the natural morphological adaptation to germinate and elongate its coleoptile under submerged flooding conditions. The phenotypic deviation associated with the tolerance to submergence at the germination stage could be due to natural variation. However, the molecular basis of this variation is still largely unknown. A comprehensive understanding of gene regulation of different genotypes that have diverse rates of coleoptile elongation can provide significant insights on improved rice varieties. To do so, publicly available transcriptome data of five rice genotypes, which have different lengths of coleoptile elongation under submergence tolerance, was analysed. The aim was to identify the correlation between promoter architecture, associated with transcriptional and hormonal regulation, in diverse genotype groups of rice that have different rates of coleoptile elongation. This was achieved by identifying the putative cis-elements present in the promoter sequences of genes upregulated in each group of genotypes (tolerant, highly tolerant and extremely tolerant genotypes). Promoter analysis identified transcription factors (TFs) that are common and unique to each group of genotypes. The candidate TFs that are common in all genotypes are MYB, bZIP, AP2/ERF, ARF, WRKY, ZnF, MADS-box, NAC, AS2, DOF, E2F, ARR-B and HSF. However, the highly tolerant genotypes interestingly possess binding sites associated with HY5 (bZIP), GBF3, GBF4 and GBF5 (bZIP), DPBF-3 (bZIP), ABF2, ABI5, bHLH and BES/BZR, in addition to the common TFs. Besides, the extremely tolerant genotypes possess binding sites associated with bHLH TFs such as BEE2, BIM1, BIM3, BM8 and BAM8, and ABF1, in addition to the TFs identified in the tolerant and highly tolerant genotypes. The transcriptional regulation of these TFs could be linked to phenotypic variation in coleoptile elongation in response to submergence tolerance. Moreover, the results indicate a crosstalk between the key TFs and phytohormones such as gibberellic acid, abscisic acid, ethylene, auxin, jasmonic acid and brassinosteroids, for an altered transcriptional regulation leading to differences in germination and coleoptile elongation under submergence. The information derived from the current in silico analysis can potentially assist in developing new rice breeding targets for direct-seeding.